Birth Stories of Trinidad and Tobago Dr. Leslie Bishop - (:unkn) unknown (The University of the West Indies, 2024)
Leslie Ann Bishop is a senior medical officer in obstetrics and gynaecology at the Scarborough Hospital. She completed her undergraduate medical training at the University of the West Indies. She also completed a Diploma in anathesia and five years of postgraduate training in Obstetric and Gynaeology in the United Kingdom. She discusses health care for expectant mothers and the benefits and risks to homebirths.
Keywords: Childbirth -- Trinidad and Tobago; Obstetricians -- Trinidad and Tobago; Maternal health services -- Trinidad and Tobago